Molecular regulation of follicle-stimulating hormone synthesis, secretion and action. (April 2018) - Das, Nandana; Kumar, T Rajendra
Abstract : Follicle-stimulating hormone (FSH) plays fundamental roles in male and female fertility. FSH is a heterodimeric glycoprotein expressed by gonadotrophs in the anterior pituitary. The hormone-specific FSHβ-subunit is non-covalently associated with the common α-subunit that is also present in the luteinizing hormone (LH), another gonadotrophic hormone secreted by gonadotrophs and thyroid-stimulating hormone (TSH) secreted by thyrotrophs. Several decades of research led to the purification, structural characterization and physiological regulation of FSH in a variety of species including humans. With the advent of molecular tools, availability of immortalized gonadotroph cell lines and genetically modified mouse models, our knowledge on molecular mechanisms of FSH regulation has tremendously expanded. Several key players that regulate FSH synthesis, sorting, secretion and action in gonads and extragonadal tissues have been identified in a physiological setting. Novel post-transcriptional and post-translational regulatory mechanisms have also been identified that provide additional layers of regulation mediating FSH homeostasis. Recombinant human FSH analogs hold promise for a variety of clinical applications, whereas blocking antibodies against FSH may prove efficacious for preventing age-dependent bone loss and adiposity. It is anticipated that several exciting new discoveries uncovering all aspects of FSH biology will soon be forthcoming.